2021
DOI: 10.1111/syen.12491
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the evolution of Ostrinia moths with phylogenomics (Pyraloidea: Crambidae: Pyraustinae)

Abstract: Reconstructing a robust phylogenetic framework is key to understanding the ecology and evolution of many economically important taxa. The crambid moth genus Ostrinia contains multiple agricultural pests, and its classification and phylogeny has remained controversial because of the paucity of characters and the lack of clear morphological boundaries for its species. To address these issues, we inferred a molecular phylogeny of Ostrinia using a phylogenomic dataset containing 498 loci and 115 197 nucleotide sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Historically, the genus was largely classified into three groups and are denoted by the letters I, II, and III, according to the morphology of male genitalia (Mutuura & Munroe 1970). However, a recent phylogenomic study confirmed the monophyly of only group III and proposed a new classification system in which the genus is divided into three new species groups (Clade I, II, and III) (Yang et al 2021). All species of group III (Mutuura & Munroe, 1970) were incorporated into Clade III, the Ostrinia nubilalis species group, along with some previously classified species in group II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the genus was largely classified into three groups and are denoted by the letters I, II, and III, according to the morphology of male genitalia (Mutuura & Munroe 1970). However, a recent phylogenomic study confirmed the monophyly of only group III and proposed a new classification system in which the genus is divided into three new species groups (Clade I, II, and III) (Yang et al 2021). All species of group III (Mutuura & Munroe, 1970) were incorporated into Clade III, the Ostrinia nubilalis species group, along with some previously classified species in group II.…”
Section: Introductionmentioning
confidence: 99%
“…Both O. furnacalis (Asian corn borer) and O. scapulalis (Adzuki bean borer), classified as group III or the new Clade III, are important agricultural pests. O. furnacalis is a significant maize pest in Asia, causing substantial economic damage, whereas O. scapulalis attacks some crops such as hops, hemp and legumes (Ishikawa et al 1999; Yang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ACB (Asian corn borer), O. furnacalis (Guenée), and the ECB (European corn borer), O. nubilalis (Hübner) (Crambidae: Pyraustinae), are worldwide maize pests that cause substantial yield losses in corn production (Bourguet et al, 2014 ; Frolov et al, 2007 ; Mutuura & Munroe, 1970 ). These two corn borers both belong to the O. nubilalis species group (trilobed uncus of male genitalia, which is a structure derived from the 10th abdominal tergite to grasp the female during copulation; see Yang et al, 2021 : 830, Clade III in Figure 1 ), one of the most evolutionarily and ecologically interesting but taxonomically difficult groups in Lepidoptera. The species group includes 10 species and 23 subspecies worldwide (Frolov et al, 2007 ; Mutuura & Munroe, 1970 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These two corn borers both belong to the O. nubilalis species group (trilobed uncus of male genitalia, which is a structure derived from the 10th abdominal tergite to grasp the female during copulation; see Yang et al, 2021 : 830, Clade III in Figure 1 ), one of the most evolutionarily and ecologically interesting but taxonomically difficult groups in Lepidoptera. The species group includes 10 species and 23 subspecies worldwide (Frolov et al, 2007 ; Mutuura & Munroe, 1970 ; Yang et al, 2021 ). Incongruence between molecular phylogenetic relationships and the traditional classification of Ostrinia has been puzzling for a long time, leading to a number of members including ACB and ECB being morphologically indistinguishable and making accurate species identification extremely difficult (Hoshizaki et al, 2008 ; Kim et al, 1999 ; Mutuura & Munroe, 1970 ; Wang et al, 2017 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation